Collective actions of platform workers - K¨ohler, Holm-Detlev (Sociología del Trabajo, 2020)
The aim of this paper is to develop a conceptual framework for analysing the collective actions and organisational practices of platform workers, building on classical approaches of the sociology of capitalist work and on the power resources theory employed in current trade union analysis. The empirical bases are recent surveys and studies on platform work, the analysis of websites for the collective action of platform workers and conversations with platform activists. The specific characteristics of platform workers’ collective actions and organisational practices are examined with a view to identifying their potential and the opportunities they afford in the light of different trade union power sources.